Inovasi Soft Cookies Kekinian dengan Tepung Ubi Jalar Ungu: Analisis Komprehensif Sifat Sensori Menggunakan Pendekatan QDA - Dyan Triana Putra; Wahyu Mafatikhul Aulia; Azis Nur Rosyid (BADAN PENERBIT STIEPARI PRESS, 2025)
This study analyzed the effect of purple sweet potato flour substitution (20%, 40%, 60%) on the organoleptic properties of soft cookies through QDA with 30 trained panelists. The results showed: (1) The purple color strengthened with increasing flour percentage due to anthocyanin pigments; (2) The characteristic aroma was optimal at 60% because the natural sugar content triggered the Maillard reaction; (3) The moist-soft texture was maintained by purple sweet potato starch; (4) The natural sweetness increased significantly. The 60% formula was superior in all aspects, while also increasing nutritional value. These findings support the use of purple sweet potato as a functional food ingredient and an alternative to wheat flour.